2017
DOI: 10.1016/j.jfda.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits adenosine deaminase and arginase activities in cadmium-induced renal toxicity in rat kidney

Abstract: In this study, the effect of enzymes involved in degradation of renal adenosine and l-arginine was investigated in rats exposed to cadmium (Cd) and treated with curcumin, the principal active phytochemical in turmeric rhizome. Animals were divided into six groups (n = 6): saline/vehicle, saline/curcumin 12.5 mg/kg, saline/curcumin 25 mg/kg, Cd/vehicle, Cd/curcumin 12.5 mg/kg, and Cd/curcumin 25 mg/kg. The results of this study revealed that the activities of renal adenosine deaminase and arginase were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…However, due to minor changes in serum creatinine level in cadmium-treated animals, it can be concluded that this metal is able to cause moderate to mild renal failure. In line with our findings, the destructive effects of cadmium on renal tissue have been reported in several studies (19,20). This evidence might be attributed to the alterations in the GFR, the threshold of tubular re-absorption, and renal blood flow.…”
Section: Discussionsupporting
confidence: 92%
“…However, due to minor changes in serum creatinine level in cadmium-treated animals, it can be concluded that this metal is able to cause moderate to mild renal failure. In line with our findings, the destructive effects of cadmium on renal tissue have been reported in several studies (19,20). This evidence might be attributed to the alterations in the GFR, the threshold of tubular re-absorption, and renal blood flow.…”
Section: Discussionsupporting
confidence: 92%
“…In literature, the beneficial action of dietary and plantderived antioxidants on toxicity of some of the heavy metals has been reported. For example, flavonoids such as epigallocatechin gallate and curcumin have been shown to possess protective activity against cadmium-induced nephrotoxicity in rats [5,6]. Catechin hydrate has been found to reduce cytotoxic and genotoxic effects of cadmium in human peripheral blood lymphocytes [7].…”
Section: Introductionmentioning
confidence: 99%
“…The use of curcumin, a bioactive agent derived from Curcuma longa rhizomes, has been used in the treatment of humans and animals because of its innumerable benefits, particularly its antimicrobial (Sarkar, De, & Mukhopadhyay, 2016), antioxidant and lipid peroxidation-protecting properties (Akinyemi et al, 2017;Momeni & Eskandari, 2017), in addition to its promotion of growth and performance in animals (Dono, 2013;Jaguezeski et al, 2018). Only in recent years have there been studies evaluating curcumin as an additive in ruminant feed (Cervantes-Valencia, Alcalá-Canto, Sumano-Lopez, Ducoing-Watty, & Gutierrez-Olvera, 2016;Jaguezeski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, during lactation, the sheep undergoes metabolic imbalances resulting in exhaustion of her antioxidant systems, causing oxidative stress, especially among breeds with high milk production (Celi, ) including the Lacaune that produces 4 L per day at peak production, the most representative breed in total world milk produced. Considering the benefits of curcumin (Akinyemi et al, ; Momeni & Eskandari, ), especially when protected by a nanocapsule structure (Catalan‐Latorre et al, ), our hypothesis was that nanocapsules of curcumin protected by Eudragit L‐100 polymer may exert benefits in both the sheep and their milk. Therefore, the objective of this study was to produce nanocapsules containing curcumin and to determine whether the addition of these formulations in the diet of dairy sheep would maintain or potentiate serum antioxidant and anti‐inflammatory effects, consequently improving milk quality.…”
Section: Introductionmentioning
confidence: 99%